The leadership handbook 26 critical lessons every leader needs - Maxwell, John C. (HarperCollins Leadership, 2008)
The most effective leaders across a wide variety of spectrums have achieved their success by beginning their journey with a question few bother to ask: How do I lead myself? As New York Times bestselling author and leadership expert John C. Maxwell says, "A leader never has to recover from a good start." So when a leader takes root by firmly establishing themselves in their field of expertise, preparing for every risk and failure imaginable, the fruit of their endeavors will spread throughout their career and impact profoundly those in whom they invest.In The Leadership Handbook, Maxwell presents 26 insights intended to help build the leader within not only those aspiring to new positions of leadership but also those veterans who aim to improve upon the steps that led them to the front of the line. Readers will enjoy and benefit immensely from Maxwell's highly relatable principles, such as:• The Best Leaders Are Listeners• Keep Your Mind on the Main Thing• Don't Manage Your Time--Manage Your Life• Keep Learning to Keep Leading• People Quit People, Not Companies• And many more!With application exercises and a "Mentoring Moment" to accompany each chapter, The Leadership Handbook presents a road map for a path many may cross but few choose to follow.